Aspectos Inflamatórios e Imunológicos de Pulpites Dentárias Humanas - BRUNO, Kely Firmino (2009)
Immune and inflammatory cells may contribute to host defense and microenvironmental changes during the pathogenesis of dental pulpitis. This study evaluated the microscopic characteristics and densities (per mm2) of tryptase+ mast cells, CD4+ T helper lymphocytes, CD45RO+ memory T lymphocytes, foxp3+ T regulatory lymphocytes, CD20+ B lymphocytes, CD68+ macrophages, and CD31+ blood vessels in human dental pulpitis (n = 38). Methods: Tryptase, CD4, CD45RO, foxp3, CD20, CD68, and CD31 expressions were analyzed using immunohistochemistry; other microscopic features, such as intensity of inflammatory infiltrate and collagen deposition, were evaluated after staining with hematoxylin and eosin. Results: Two microscopic patterns of dental pulpitis were found: group 1 (G1) (n = 15) showed intense inflammatory infiltrate and mild collagen deposition; conversely, group 2 (G2) (n = 23) showed scarce inflammatory infiltrate and intense collagen deposition. The numbers of CD68+ and CD20+ cells and the density of blood vessels were higher in G1 than in G2. However, there were no differences in CD4+ and CD45RO+ cell densities between groups. When present, mast cells were equally distributed in G1 and G2, whereas foxp3+ cells were detected in 58.82% and 14.28% of the samples of G1 and G2. Conclusions: Immune and inflammatory cell infiltration have different patterns in human dental pulpitis, which might reflect distinct microscopic characteristics and particular local defense capabilities.